Crystallization and preliminary X-ray diffraction studies of BnSP-6, a myotoxic phospholipase A2 from Bothrops neuwiedi venom - Fontes, MRM; Monteiro, L. E.; Soares, A. M.; Rodrigues, V. M.; da Silva, R. J.; Giglio, JR (Bentham Science Publ Ltd, 2000)
BnSP-6 (myotoxin I) is a phospholipase A2 homologue isolated from Bothrops neuwiedi pauloensis venom. Crystals of BnSP-6 were obtained which diffracted X-rays to 2.5 Angstrom resolution using a synchrotron radiation source at room temperature and belong to space group P3(1)21. The unit cell dimensions are a=b=57.7, c=131.1 Angstrom. The structure was solved by molecular replacement using the coordinates of bothropstoxin I from B. jararacussu venom. There are two molecules in the asymmetric unit.